Remedial Measures to Rectify Blackspot on National Highway - Pallavi Patil; Nagesh Suryawanshi; Sushma Kulkarni (Universitas Pendidikan Indonesia (UPI), 2021)
Road safety becomes a major concern for the regulatory authorities in India. Indian road safety situation is many times worse when compared to the developed countries of the world, leaving much to be done in the field of Road Safety Management. Road safety is defined as the absence of crashes, injuries, and fatalities. The term